The Relationship of School Participation with Motor Proficiency and Executive Function in Children with Autism Spectrum Disorder - kheirollahzadeh, mahsa; alizadeh zarei, mehdi; amini, malek; dehghan tazarjani, faezeh (Iranian Journal of Child Neurology, 2021)
Abstract Objective participation in meaningful activities are important aspects of development in children with developmental disorder such as autism spectrum disorder. The purpose of this study was to assess the correlation of school participation with motor proficiency and executive function in children with Autism Spectrum Disorder. Materials & Methods In this cross-sectional (descriptive-analytic) study, 52 students aged 6 to 12 years old with ASD were selected through the convenience sampling method. The GARS-2 scale was used to confirm ASD diagnosis. Other psychiatric comorbidities such as ADHA were studied by the CSI-4 tool, and students with comorbidities were excluded. Data were collected using SFA, BOTMP-2, and BRIEF questionnaires. It should be noted that in the BRIEF questionnaire, a higher score indicates a more severe disability Results Our findings showed that motor proficiency and its components had a significant direct correlation with school participation in childrenwith ASD (P ≤0.001). On the other hand, school participation was inversely and significantly correlated with the behavioral regulation and metacognition monitoring indices of the executive function dimension (P <0.05). Conclusion Based on the findings of this research, the development of motor proficiency and improvements in the behavioral regulation andmetacognition monitoring of students with ASD will boost their participation in school activities. Motor proficiency was significantly correlated with school participation in children with ASD. More attention should be paid to perceptual motor interventions and cognitive rehabilitation programs (with a focus on monitoring metacognition and shifting behavioral regulation) to increase the participation of children with ASD in school activities.